KEGIATAN PELAKSANAAN PEMELIHARAAN TANAM POHON KAMPUNG BUNGA WARNA WARNI DI DESA SUKALAKSANA RW.01 RT.016 - Lina Marlina (Lembaga Pengembangan, Penelitian dan Pengabdian Kepada Masyarakat Universitas Banten Jaya, 2021)
Community service activities in the implementation of the maintenance of planting colorful flower village trees in Sukalaksana Village RW.01 RT.016 as a form of environmental conservation that needs to be cultivated, this activity is carried out with the involvement of the Sukalaksana Village community, Youth Organizations, and a team of KKM Students Group 11 UNBAJA 2021. The Maintenance of Planting Colorful Flower Village Trees in Sukalaksana Village RW.01 RT.016 is expected to be able to make the first tap of public awareness to have concern for the environment, especially in this flower village or also called by its original name Kaningan village. This activity not only aims to realize reforestation in Sukalaksana village, but it is also one of the work programs of the 2021 Unbaja Group 11 KKM team, In this community service program method, the team uses an activity method with several stages, namely the Planting Planning stage, Planting Preparation, Determination of Candidate Locations, Need for Number of Seeds, Planting Design, namely the preparation and selection of plant types. Next is tree planting, namely the stage of the tree planting process, from this community service the results obtained are increasing public awareness to have a concern for the environment and nature conservation, especially in this flower village in Sukalaksana Village.